Respiratory Failure due to Possible Donor-Derived Sporothrix schenckii Infection in a Lung Transplant Recipient - Nathan C. Bahr; Katherine Janssen; Joanne Billings; Gabriel Loor; Jaime S. Green (Case Reports in Infectious Diseases)
Background. De novo and donor-derived invasive fungal infections (IFIs) contribute to morbidity and mortality in solid organ transplant (SOT) recipients. Reporting of donor-derived IFIs (DDIFIs) to the Organ Procurement Transplant Network has been mandated since 2005. Prior to that time no systematic monitoring of DDIFIs occurred in the United States. Case Presentation. We report a case of primary graft dysfunction in a 49-year-old male lung transplant recipient with diffuse patchy bilateral infiltrates likely related to pulmonary Sporothrix schenckii infection. The organism was isolated from a bronchoalveolar lavage on the second day after transplantation. Clinical and radiographic responses occurred after initiation of amphotericin B lipid formulation. Conclusion. We believe that this was likely a donor-derived infection given the early timing of the Sporothrix isolation after transplant in a bilateral single lung transplant recipient. This is the first case report of sporotrichosis in a lung transplant recipient. Our patient responded well to amphotericin induction therapy followed by maintenance therapy with itraconazole. The implications of donor-derived fungal infections and Sporothrix in transplant recipients are reviewed. Early recognition and management of these fungi are essential in improving outcomes.